Wang‐Koch formula for optimization of intraocular lens power calculation: Evaluation at a Canadian center. Issue 1 (January 2018) - Popovic, Marko; Schlenker, Matthew B.; Campos‐Möller, Xavier; Pereira, Austin; Ahmed, Iqbal Ike K.
Abstract : Purpose : To externally validate the Wang‐Koch method for optimization of intraocular lens (IOL) formulas. Setting : TLC Laser Eye Centre, Mississauga, Ontario, Canada. Design : Retrospective case series. Methods : Consecutive cataract patients with an axial length (AL) of 25.0 mm or longer were recruited. The predicted postoperative spherical equivalents (SEs) calculated from the Holladay 1 formula were compared with the 3‐week postoperative SEs to yield prediction errors for Wang‐Koch adjusted and unadjusted ALs. A mixed linear model was used to compare the proportion of eyes with a prediction error of ±0.25 diopter (D) or worse, ±0.50 D or worse, and ±1.00 D or worse between groups. The secondary outcomes of mean absolute error and median absolute error were also analyzed. A subgroup analysis was performed based on AL subgroups. Results : Two hundred sixty‐two eyes were selected for inclusion with a balanced sex distribution, a mean age of 62.49 years ± 9.13 (SD), and a preoperative AL of 26.49 ± 1.10 mm. Subgroup prediction error comparisons of ±0.50 D or worse favored unadjusted eyes with ALs between 25.0 mm and 26.0 mm (n = 105; P < .001), no difference in eyes with ALs between 26.0 mm and 27.0 mm (n = 91; P = .43), adjusted eyes with ALs between 27.0 mm and 28.0 mm (n = 36; P = .003), and adjusted eyes with ALs of 28.00 mm or longer (n = 30; P < .001). Conclusion : The Wang‐Koch adjustment should only be applied in eyes with ALs longer than 27.0 mm that have IOL power calculation with the Holladay 1 formula.